Falls and confidence related quality of life outcome measures in an older British cohort. Issue 904 (1st February 2001) - Parry, S W; Steen, N; Galloway, S R; Kenny, R A; Bond, J
Abstract : Falls are common in older subjects and result in loss of confidence and independence. The Falls Efficacy Scale (FES) and the Activities-specific Balance Confidence scale (ABC) were developed in North America to quantify these entities, but contain idiom unfamiliar to an older British population. Neither has been validated in the UK. The FES and the ABC were modified for use within British culture and the internal consistency and test-retest reliability of the modified scales (FES-UK and ABC-UK) assessed. A total of 193 consecutive, ambulant, new, and return patients (n=119; 62%) and their friends and relatives ("visitors", n=74; 38%) were tested on both scales, while the last 60 subjects were retested within one week. Internal reliability was excellent for both scales (Cronbach's alpha 0.97 (FES-UK), and 0.98 (ABC-UK)). Test-retest reliability was good for both scales, though superior for the ABC-UK (intraclass correlation coefficient 0.58 (FES-UK), 0.89 (ABC-UK)). There was evidence to suggest that the ABC-UK was better than the FES-UK at distinguishing between older patients and younger patients (‖ t ABC ‖ = 4.4; ‖ t FES ‖ = 2.3); and between fallers and non-fallers (‖ t ABC ‖ = 8.7; ‖ t FES ‖ = 5.0) where the t statistics are based on the comparison of two independent samples. The ABC-UK and FES-UK are both reliable and valid measures for the assessment of falls and balance related confidence in older adults. However, better test-retest reliability and more robust differentiation of subgroups in whom falls related quality of life would be expected to be different make the ABC-UK the current instrument of choice in assessing this entity in older British subjects.